Age-related differences in the effect of intermittent fasting on the morphofunctional parameters of the rat’s pancreas - Yanko, R.V. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2024)
The effectiveness of using intermittent fasting (IF) to activate pancreas function is not clear. One of the reasons for this may be differences in the use of IF mode, the duration of the experiment, as well as the involvement of animals of different ages in the experiment. Also, the question of how pronounced is the effect of the use of IF to increase the functional activity of the pancreas in the elderly remains open. The aim of the work was to investigate and compare the morphofunctional changes in the pancreas of rats of different ages after exposure to IF and to evaluate the prospects of its use as a means to correct pronounced age-related decreases in gland function. Experiments were performed on 40 male rats aged 3 and 15 months. Experimental animals were exposed to IF, namely, 1 day – complete fasting / 2 days – standard diet. Access to water was free. The duration of the experiment was 28 days. Histological preparations were made from pancreas tissue according to the standard method. Histomorphometry was carried out using the computer program "Image J". Research was conducted in accordance with the provisions of the "European Convention for the Protection of Vertebrate Animals Used for Experimental and Other Scientific Purposes" (Strasbourg, 1986). It was found that exposure to IF for 28 days led to the appearance of clearly expressed morphofunctional signs of increased activity of the pancreas in adult rats. The endocrine function of the gland increased in particular, as evidenced by a probable increase in the relative area of the endocrine part (by 108%), the average number of Langerhans islets (by 44%), the size of the islets, the number of endocrinocytes located in them (by 20%), and a decrease in the concentration of glucose in the blood. In young animals, on the contrary, IF reduced the activity of both exo- and endocrine (to a greater extent) part of the gland. The effect of IF reduced the amount of connective tissue in the pancreas of rats of different ages. The obtained data can be used to improve the function of the pancreas in adults and the elderly, as well as in the prevention of age-related chronic diseases of the gland accompanied by the appearance of fibrosis. At the same time, the use of IF at a young age is not desirable.